2021
DOI: 10.48550/arxiv.2107.14640
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermodynamic Geometry of Black Holes Enclosed by a Cavity in Extended Phase Space

Peng Wang,
Feiyu Yao

Abstract: Recently, the phase space of black holes in a spherical cavity of radius rB has been extended by introducing a thermodynamic volume V ≡ 4πr 3 B /3. In the extended phase space, we consider the thermodynamic geometry, which provides a powerful tool to understand the microscopic structure of black holes, of Reissner-Nordström (RN) black holes in a cavity, as well as that of Reissner-Nordström-AdS black holes. Although the phase structures of the cavity and AdS cases show striking resemblance, we find that there … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…In Refs. [38][39][40], they extended the phase space of SC, R-N and Gauss-Bonnet black holes in the cavity, and then investigated the thermodynamic properties and P −V criticality of those black holes. The results showed that the black hole systems have Hawking-Pagelike phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [38][39][40], they extended the phase space of SC, R-N and Gauss-Bonnet black holes in the cavity, and then investigated the thermodynamic properties and P −V criticality of those black holes. The results showed that the black hole systems have Hawking-Pagelike phase transition.…”
Section: Introductionmentioning
confidence: 99%